Impact of Chronic Kidney Disease on Outcomes of Primary PCI - Khan, Muhammad Idrees; Hameed Ullah; Khan, Naveed Ahmad; Spogmai; Ahmad, Sohail; Orakzai, Muhammad Hafeez (Indus Journal of Bioscience Research, 2024)
Objective: To assess the impact of chronic kidney disease (CKD) on outcomes, including major adverse cardiac events (MACE) and mortality, in patients undergoing primary percutaneous coronary intervention (PCI) at the Hayatabad Medical Complex, Peshawar.Methodology:  A prospective cohort study was conducted from September 2022, to April 2023. A total of 250 patients were enrolled, divided into two groups: 125 patients with CKD (eGFR